Services of Economic Development Organisations in Győr - Adrienn Reisinger; Petra Kecskés; Katalin Czakó (DETUROPE)
Economic development of a municipality is highly depended on organizations and institutions, which services target local entrepreneurs and other economic actors. In the summer of 2015 we have collected and mapped the services of organizations with the function of economic development in the Hungarian city, Győr. Through our research we could identify the services and the characteristics of linkages and cooperation of the economic development organizations (EDOs). Most important findings of the study are the followings: activity of the organizations has a wide range. Some of them are presented in more organizations at the same time. Level of diversification is quite low. Directions of cooperation are mainly based on personal or ad hoc relations. We conducted that EDOs know about each other, despite of this fact the number of linkages is low. In this paper we provide findings about Győr, but the results can be used for other settlements’ economic development, too.